2015
DOI: 10.1073/pnas.1424329112
|View full text |Cite
|
Sign up to set email alerts
|

Defining and identifying Sleeping Beauties in science

Abstract: A Sleeping Beauty (SB) in science refers to a paper whose importance is not recognized for several years after publication. Its citation history exhibits a long hibernation period followed by a sudden spike of popularity. Previous studies suggest a relative scarcity of SBs. The reliability of this conclusion is, however, heavily dependent on identification methods based on arbitrary threshold parameters for sleeping time and number of citations, applied to small or monodisciplinary bibliographic datasets. Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
316
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(330 citation statements)
references
References 52 publications
3
316
1
10
Order By: Relevance
“…The literature has showed a difference of scientific production across countries, citations of articles, and coauthored papers among countries/research institutions for various fields of science (6,12,14,(16)(17)(18). The pioneering study by Frame and Carpenter (14) showed, using the data from the 1973 Science Citation Index, that basic fields (e.g., physics) have higher levels of international collaboration than predominantly applied fields (e.g., engineering/technology).…”
mentioning
confidence: 99%
“…The literature has showed a difference of scientific production across countries, citations of articles, and coauthored papers among countries/research institutions for various fields of science (6,12,14,(16)(17)(18). The pioneering study by Frame and Carpenter (14) showed, using the data from the 1973 Science Citation Index, that basic fields (e.g., physics) have higher levels of international collaboration than predominantly applied fields (e.g., engineering/technology).…”
mentioning
confidence: 99%
“…Revival of old, dormant ideas has also been common. These "sleeping beauties" involve a proposal of a scientific idea "ahead of its time", and thus with little immediate fanfare, only to be "rediscovered" and revived many years later [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics are commonly used for this kind of performance evaluations (2)(3)(4)(5)(6)(7), and the volume of grant income is also generally seen as a good indicator of performance. Although many studies have examined the collaboration patterns originating from publication information (8)(9)(10)(11)(12)(13)(14), little is known about the characteristics of project collaborations supported by research funding, which is undoubtedly a type of research output in its own right, but also the origin of other research outputs.…”
mentioning
confidence: 99%